Emergency medicine physician supervision and mortality among patients receiving care from non-physician clinicians in a task-sharing model of emergency care in rural Uganda: a retrospective analysis of a single-centre training programme. Issue 6 (29th June 2022) - Rice, Brian; Pickering, Ashley; Laurence, Colleen; Kizito, Prisca Mary; Leff, Rebecca; Kisingiri, Steven Jonathan; Ndyamwijuka, Charles; Nakato, Serena; Adriko, Lema Felix; Bisanzo, Mark
Abstract : Objectives: To assess the association between emergency medicine physician supervision and 3-day mortality for patients receiving care from non-physician clinicians in a task-sharing model of emergency care in rural Uganda. Design: Retrospective cohort analysis with multivariable logistic regression. Setting: Single rural Ugandan emergency unit. Participants: All patients presenting for care from 2009 to 2019. Interventions: Three cohorts of patients receiving care from non-physician clinicians had three different levels of physician supervision: 'Direct Supervision' (2009–2010) emergency medicine physicians directly supervised all care; 'Indirect Supervision' (2010–2015) emergency medicine physicians were consulted as needed; 'Independent Care' (2015–2019) no emergency medicine physician supervision. Primary outcome measure: Three-day mortality. Results: 38 033 ED visits met inclusion criteria. Overall mortality decreased significantly across supervision cohorts ('Direct' 3.8%, 'Indirect' 3.3%, 'Independent' 2.6%, p<0.001), but so too did the rates of patients who presented with ≥3 abnormal vitals ('Direct' 32%, 'Indirect' 19%, 'Independent' 13%, p<0.001). After controlling for vital sign abnormalities, 'Direct' and 'Indirect' supervision were both significantly associated with reduced OR for mortality ('Direct': 0.57 (0.37 to 0.90), 'Indirect': 0.71 (0.55 to 0.92)) when compared with 'Independent Care'. Sensitivity analysis showed that this mortality benefit was significant for the minority of patients (17.2%) with ≥3 abnormal vitals ('Direct': 0.44 (0.22 to 0.85), 'Indirect': 0.60 (0.41 to 0.88)), but not for the majority (82.8%) with two or fewer abnormal vitals ('Direct': 0.81 (0.44 to 1.49), 'Indirect': 0.82 (0.58 to 1.16)). Conclusions: Emergency medicine physician supervision of emergency care non-physician clinicians is independently associated with reduced overall mortality. This benefit appears restricted to the highest risk patients based on abnormal vitals. With over 80% of patients having equivalent mortality outcomes with independent non-physician clinician emergency care, a synergistic model providing variable levels of emergency medicine physician supervision or care based on patient acuity could safely address staffing shortages.